Synthesis and Application of an Aldazine-Based Fluorescence Chemosensor for the Sequential Detection of Cu2+ and Biological Thiols in Aqueous Solution and Living Cells - Hongmin Jia; Ming Yang; Qingtao Meng; Guangjie He; Yue Wang; Zhizhi Hu; Run Zhang; Zhiqiang Zhang (Sensors, 2016)
A fluorescence chemosensor, 2-hydroxy-1-naphthaldehyde azine (HNA) was designed and synthesized for sequential detection of Cu2+ and biothiols. It was found that HNA can specifically bind to Cu2+ with 1:1 stoichiometry, accompanied with a dramatic fluorescence quenching and a remarkable bathochromic-shift of the absorbance peak in HEPES buffer. The generated HNA-Cu2+ ensemble displayed a “turn-on” fluorescent response specific for biothiols (Hcy, Cys and GSH) based on the displacement approach, giving a remarkable recovery of fluorescence and UV-Vis spectra. The detection limits of HNA-Cu2+ to Hcy, Cys and GSH were estimated to be 1.5 μM, 1.0 μM and 0.8 μM, respectively, suggesting that HNA-Cu2+ is sensitive enough for the determination of thiols in biological systems. The biocompatibility of HNA towards A549 human lung carcinoma cell, was evaluated by an MTT assay. The capability of HNA-Cu2+ to detect biothiols in live A549 cells was then demonstrated by a microscopy fluorescence imaging assay.